Copper-based heat conduction material and preparation method thereof

By covering metal copper on the surface of modified graphene and silicon carbide and combining it with copper-based materials, the problem of poor interface bonding of existing copper-based materials reinforced materials is solved, and the thermal conductivity and bending strength of the material are significantly improved.

CN119506651APending Publication Date: 2025-02-25ANHUI XUJING POWDER NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411704482.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

After the existing copper-based materials are added, the interface bond between the reinforcement material and the copper matrix is ​​poor, resulting in insufficient strength and thermal conductivity of the material.

Method used

The use of coated modified graphene and coated silicon carbide is used to improve its compatibility and bonding power with the copper matrix by coating metal copper on the surface of modified graphene and silicon carbide.

Benefits of technology

The thermal conductivity and bending strength of the copper-based material are significantly improved, and the overall performance of the material is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of copper-based materials, in particular to a copper-based heat conduction material and a preparation method thereof.The copper-based heat conduction material comprises the following raw materials of 15%-20% of coated modified graphene, 5%-10% of coated silicon carbide and the balance copper powder; the specific preparation method comprises the following steps: stirring and mixing the coated modified graphene, the coated silicon carbide and the copper powder to prepare the copper-based heat-conducting material. Through combined use of coated modified graphene and coated silicon carbide, the heat conductivity and bending strength of the copper-based material are improved; the surfaces of the modified graphene and the silicon carbide are coated with the metal copper, the modified graphene and the silicon carbide can be better compatible with a copper matrix, after sintering treatment, the modified graphene and the silicon carbide are evenly dispersed in the copper matrix, the binding force of the modified graphene and the silicon carbide is improved, and therefore the overall performance of the copper-based material can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-based materials, in particular to a copper-based thermal conductive material and a preparation method thereof. Background Art

[0002] Copper-based materials are a type of material with special properties that is made by adding other materials or using special processes based on copper as the basic element. This type of material not only has good electrical conductivity, thermal conductivity and plasticity, but also has higher strength, hardness, wear resistance, corrosion resistance and other excellent properties through technological innovation. These unique properties make copper-based materials have broad application prospects in aerospace, electronic information, transportation, energy and environmental protection and other fields.

[0003] At present, the strength and thermal conductivity of copper-based materials are generally improved by adding reinforcing materials such as diamond, carbon nanotubes, graphene, graphite sheets, carbon fibers or alumina to the copper matrix. However, the above reinforcing materials are prone to agglomeration when mixed with copper powder, making it difficult to evenly disperse them in the copper powder; and after sintering, the interface bonding between the reinforcing materials and the copper matrix is ​​also poor, thereby affecting the quality of the copper-based powder material. Based on this, a copper-based thermal conductive material and a preparation method thereof are proposed. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the present invention provides a copper-based thermal conductive material and a preparation method thereof, which improves the thermal conductivity and bending strength of the copper-based material by using a combined coating of modified graphene and coated silicon carbide.

[0005] To achieve the above object, the present invention provides the following technical solution: a copper-based thermal conductive material, comprising the following raw materials, by mass percentage: 15-20% of coated modified graphene, 5-10% of coated silicon carbide, and the balance of copper powder;

[0006] The coated modified graphene and coated silicon carbide are obtained by coating copper on the surfaces of the modified graphene and silicon carbide.

[0007] Preferably, the modified graphene is prepared as follows: S11, dispersing graphene in o-dichlorobenzene to form a suspension; S12, dissolving 4-aminothiophenol in 45wt% acetonitrile solution, then adding it to the suspension, introducing nitrogen to maintain an inert atmosphere, then adding isoamyl nitrite, stirring the reaction at 60-70°C for 18-24h, cooling to room temperature, and obtaining a reaction material; S13, diluting the reaction material with N,N-dimethylformamide, filtering, washing, and drying under vacuum to obtain modified graphene.

[0008] Preferably, in step S11, the material-liquid ratio of graphene to o-dichlorobenzene is 1:1.2 mg / ml.

[0009] Preferably, in step S12, the solid-liquid ratio of the 4-aminothiophenol and the acetonitrile solution is 1:15 g / ml; the volume ratio of the acetonitrile solution and o-dichlorobenzene is 1:2, and the volume ratio of the acetonitrile solution and isoamyl nitrite is 7:1.

[0010] Preferably, the coated modified graphene or coated silicon carbide is prepared as follows: S21, dissolving copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate in deionized water, heating to 75-85°C, and adjusting the pH of the system to 9-10 with 30wt% sodium hydroxide solution to obtain a dissolved solution; S22, adding modified graphene or silicon carbide and 37wt% formaldehyde solution to the dissolved solution, stirring continuously, and continuing to stir for 15-30 minutes after bubbles appear to obtain a composite solution; S23, filtering, washing and drying the composite solution in sequence to obtain a coated modified graphene or coated silicon carbide.

[0011] Preferably, in step S21, the mass ratio of copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate is 1:1:2; and the material-liquid ratio of copper sulfate pentahydrate-disodium ethylenediaminetetraacetate-sodium tartrate and deionized water is 1:3.

[0012] Preferably, in step S22, the amount of modified graphene or silicon carbide added is 40-50% of the mass of the dissolving solution; and the amount of formaldehyde solution used is 8 ml / L.

[0013] Preferably, the particle size of the copper powder is 4-5 μm; the particle size of the coated modified graphene is 1-2 μm; and the particle size of the coated silicon carbide is 2-3 μm.

[0014] The present invention also provides a method for preparing a copper-based thermal conductive material, which specifically comprises: mixing coated modified graphene, coated silicon carbide and copper powder to prepare the copper-based thermal conductive material.

[0015] The present invention provides a copper-based thermal conductive material and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0016] The present invention improves the thermal conductivity and bending strength of copper-based materials by using coated modified graphene and coated silicon carbide in combination; wherein, by coating the surfaces of modified graphene and silicon carbide with metallic copper, the two can be better compatible with the copper matrix, and after sintering treatment, the modified graphene and silicon carbide are evenly dispersed in the copper matrix, and the bonding force between each other is improved, thereby enhancing the overall performance of the copper-based material.

[0017] The present invention obtains mercaptobenzene functionalized graphene by modifying graphene, so that a rigid heat bridge is established between the graphene and the copper interface through the mercaptobenzene molecular structure, and electrons tunnel between the graphene and the copper matrix through the rigid heat bridge, which can further improve the thermal conductivity of the copper-based material. DETAILED DESCRIPTION

[0018] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0019] Example 1

[0020] The preparation of modified graphene is as follows:

[0021] S11. Dispersing graphene in o-dichlorobenzene to form a suspension; controlling the solid-liquid ratio of graphene to o-dichlorobenzene to be 1:1.2 mg / ml.

[0022] S12, dissolving 4-aminobenzenethiol in 45 wt % acetonitrile solution, then adding it to the suspension, introducing nitrogen to maintain an inert atmosphere, then adding isoamyl nitrite, stirring and reacting at 60° C. for 24 h, and cooling to room temperature to obtain a reaction material;

[0023] The solid-liquid ratio of the above 4-aminothiophenol and acetonitrile solution is 1:15 g / ml; the volume ratio of the acetonitrile solution and o-dichlorobenzene is 1:2, and the volume ratio of the acetonitrile solution and isoamyl nitrite is 7:1.

[0024] S13, diluting the reaction material with N,N-dimethylformamide, filtering, washing and drying under vacuum to obtain modified graphene.

[0025] Example 2

[0026] The preparation of modified graphene is as follows:

[0027] S11. Dispersing graphene in o-dichlorobenzene to form a suspension; controlling the solid-liquid ratio of graphene to o-dichlorobenzene to be 1:1.2 mg / ml.

[0028] S12, dissolving 4-aminobenzenethiol in 45 wt % acetonitrile solution, then adding it to the suspension, introducing nitrogen to maintain an inert atmosphere, then adding isoamyl nitrite, stirring and reacting at 70° C. for 18 h, and cooling to room temperature to obtain a reaction material;

[0029] The solid-liquid ratio of the above 4-aminothiophenol and acetonitrile solution is 1:15 g / ml; the volume ratio of the acetonitrile solution and o-dichlorobenzene is 1:2, and the volume ratio of the acetonitrile solution and isoamyl nitrite is 7:1.

[0030] S13, diluting the reaction material with N,N-dimethylformamide, filtering, washing and drying under vacuum to obtain modified graphene.

[0031] Example 3

[0032] The preparation of coated modified graphene is as follows:

[0033] S21, dissolving copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate in deionized water, heating to 85° C., and adjusting the pH of the system to 9 with a 30 wt % sodium hydroxide solution to obtain a solution;

[0034] The mass ratio of the above copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate is 1:1:2; and the material-liquid ratio of copper sulfate pentahydrate-disodium ethylenediaminetetraacetate-sodium tartrate and deionized water is 1:3.

[0035] S22, adding the modified graphene in Example 1 and 37 wt % formaldehyde solution into the dissolving solution, stirring continuously, and stirring for 30 min after bubbles appear to obtain a composite solution;

[0036] In the above-mentioned Example 1, the amount of modified graphene added is 40% of the mass of the dissolving solution; the amount of formaldehyde solution used is 8 ml / L.

[0037] S23, filtering, washing and drying the composite liquid in sequence to obtain coated modified graphene.

[0038] The preparation method of the coated silicon carbide is the same as that of the above-mentioned coated modified graphene.

[0039] Example 4

[0040] The preparation of coated modified graphene or coated silicon carbide is as follows:

[0041] S21, dissolving copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate in deionized water, heating to 75° C., and adjusting the pH of the system to 10 with a 30 wt % sodium hydroxide solution to obtain a solution;

[0042] The mass ratio of the above copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate is 1:1:2; and the material-liquid ratio of copper sulfate pentahydrate-disodium ethylenediaminetetraacetate-sodium tartrate and deionized water is 1:3.

[0043] S22, adding the modified graphene or silicon carbide in Example 2 and 37 wt % formaldehyde solution to the dissolving solution, stirring continuously, and stirring for 15 min after bubbles appear to obtain a composite solution;

[0044] In the above-mentioned Example 2, the amount of modified graphene or silicon carbide added is 50% of the mass of the dissolving solution; the amount of formaldehyde solution used is 8 ml / L.

[0045] S23, filtering, washing, and drying the composite liquid in sequence to obtain coated modified graphene or coated silicon carbide.

[0046] The preparation method of the coated silicon carbide is the same as that of the above-mentioned coated modified graphene.

[0047] Example 5

[0048] A copper-based thermal conductive material, comprising the following raw materials, measured by mass percentage: 15% of the coated modified graphene (particle size 1-2 μm) in Example 3, 10% of the coated silicon carbide (particle size 2-3 μm) in Example 3, and the remainder is copper powder (4-5 μm);

[0049] The preparation method of the copper-based thermal conductive material is as follows: the coated modified graphene, the coated silicon carbide and the copper powder are stirred and mixed to obtain the copper-based thermal conductive material.

[0050] Example 6

[0051] A copper-based thermal conductive material, comprising the following raw materials, by mass percentage: 20% of the coated modified graphene (particle size 1-2 μm) in Example 3, 5% of the coated silicon carbide (particle size 2-3 μm) in Example 3, and the remainder is copper powder (4-5 μm);

[0052] The preparation method of the copper-based thermal conductive material is as follows: the coated modified graphene, the coated silicon carbide and the copper powder are stirred and mixed to obtain the copper-based thermal conductive material.

[0053] Example 7

[0054] A copper-based thermal conductive material, comprising the following raw materials, measured by mass percentage: 18% of the coated modified graphene (particle size 1-2 μm) in Example 3, 7% of the coated silicon carbide (particle size 2-3 μm) in Example 3, and the remainder is copper powder (4-5 μm);

[0055] The preparation method of the copper-based thermal conductive material is as follows: the coated modified graphene, the coated silicon carbide and the copper powder are stirred and mixed to obtain the copper-based thermal conductive material.

[0056] Comparative Example 1

[0057] A copper-based thermal conductive material, comprising the following raw materials, measured by mass percentage: 18% of the modified graphene (particle size 1.2 μm) in Example 1, 7% of silicon carbide (particle size 2-3 μm), and the remainder of copper powder (4-5 μm);

[0058] The preparation method of the copper-based thermal conductive material is: mixing the modified graphene, silicon carbide and copper powder to obtain the copper-based thermal conductive material.

[0059] Comparative Example 2

[0060] A copper-based thermal conductive material and a preparation method thereof are substantially the same as those in Example 7, except that the coated modified graphene (particle size 1-2 μm) in Example 3 is replaced with coated graphene (particle size 1-2 μm). The preparation of the coated graphene (particle size 1-2 μm) is as follows:

[0061] ①, dissolve copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate in deionized water, heat to 85°C, and adjust the pH of the system to 9 with 30wt% sodium hydroxide solution to obtain a solution;

[0062] The mass ratio of the above copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate is 1:1:2; and the material-liquid ratio of copper sulfate pentahydrate-disodium ethylenediaminetetraacetate-sodium tartrate and deionized water is 1:3.

[0063] ②, add graphene and 37wt% formaldehyde solution into the dissolving solution, continue stirring, and continue stirring for 30 minutes after bubbles appear to obtain a composite solution;

[0064] The added amount of the above graphene is 40% of the mass of the dissolving solution; the amount of formaldehyde solution is 8 ml / L.

[0065] ③. The composite liquid is filtered, washed and dried in sequence to obtain coated graphene.

[0066] Comparative Example 3

[0067] A copper-based thermal conductive material comprises the following raw materials, measured by mass percentage: 18% of the coated modified graphene (particle size 1-2 μm) in Example 3, and the remainder is copper powder (4-5 μm);

[0068] The preparation method of the copper-based thermal conductive material is as follows: the coated modified graphene and copper powder are stirred and mixed to obtain the copper-based thermal conductive material.

[0069] Quality Inspection

[0070] The copper-based thermal conductive materials in Examples 5-7 and Comparative Examples 1-3 were used as test samples to conduct thermal conductivity and strength tests. The specific test results are shown in the following table.

[0071] 1. Place the sample in a mold and press it to a size of 4mm×4mm×40mm, then place it in a resistance furnace for sintering, heating it to 800℃ at a rate of 30℃ / min and keeping it warm for 1h, and then cool it to room temperature with the furnace after the insulation is completed. Use a universal mechanical testing machine to test the bending strength.

[0072] 2. Use a laser thermal conductivity meter to test the thermal diffusion coefficient α of the composite material, and use the heating performance of the instrument to test the thermal conductivity of the sample. Calculate the thermal conductivity of the sample according to the following formula: λ = α × Cp ×ρ. Density ρ is obtained by the water displacement method, and specific heat capacity C p Measured by differential scanning calorimetry.

[0073] Table 1 Thermal conductivity and flexural strength

[0074] category Thermal conductivity, W / (m·K) Flexural strength, MPa Example 5 678 75 Example 6 690 74 Example 7 685 77 Comparative Example 1 513 64 Comparative Example 2 622 73 Comparative Example 3 682 58

[0075] From the above table we can know:

[0076] (1) Compared with Example 7, the thermal conductivity and flexural strength of the material in Comparative Example 1 are significantly reduced, indicating that copper coating of modified graphene and silicon carbide is conducive to uniform dispersion of the two and better combination with the copper matrix, thereby improving the performance of the material.

[0077] (2) Compared with Example 7, the bending strength of the material in Comparative Example 2 is similar, but the thermal conductivity is slightly worse, indicating that modifying the graphene is beneficial to enhancing the thermal conductivity of the material.

[0078] (3) Compared with Example 7, the thermal conductivity of the material in Comparative Example 3 is similar, but the bending strength is significantly reduced, indicating that the use of coated silicon carbide can greatly improve the strength of the material.

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A copper-based thermal conductive material, characterized in that: The raw materials include, by mass percentage, 15-20% of coated modified graphene, 5-10% of coated silicon carbide, and the balance of copper powder; The coated modified graphene and coated silicon carbide are obtained by coating copper on the surfaces of the modified graphene and silicon carbide.

2. The copper-based thermal conductive material according to claim 1, characterized in that: The preparation of the modified graphene is as follows: S11, dispersing graphene in o-dichlorobenzene to form a suspension; S12, dissolving 4-aminobenzenethiol in 45 wt% acetonitrile solution, then adding it to the suspension, introducing nitrogen to maintain an inert atmosphere, then adding isoamyl nitrite, stirring and reacting at 60-70° C. for 18-24 h, and cooling to room temperature to obtain a reaction material; S13, diluting the reaction material with N,N-dimethylformamide, filtering, washing and drying under vacuum to obtain modified graphene.

3. The copper-based thermal conductive material according to claim 2, characterized in that: In step S11, the material-liquid ratio of graphene to o-dichlorobenzene is 1:1.2 mg / ml.

4. The copper-based thermal conductive material according to claim 2, characterized in that: In step S12, the solid-liquid ratio of the 4-aminothiophenol and the acetonitrile solution is 1:15 g / ml; the volume ratio of the acetonitrile solution to o-dichlorobenzene is 1:2, and the volume ratio of the acetonitrile solution to isoamyl nitrite is 7:

1.

5. The copper-based thermal conductive material according to claim 2, characterized in that: The preparation of the coated modified graphene or coated silicon carbide is as follows: S21, dissolving copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate in deionized water, heating to 75-85° C., and adjusting the pH of the system to 9-10 with 30 wt % sodium hydroxide solution to obtain a solution; S22, adding modified graphene or silicon carbide and 37 wt % formaldehyde solution to the dissolving solution, stirring continuously, and continuing stirring for 15-30 min after bubbles appear to obtain a composite solution; S23, filtering, washing, and drying the composite liquid in sequence to obtain coated modified graphene or coated silicon carbide.

6. The copper-based thermal conductive material according to claim 5, characterized in that: In step S21, the mass ratio of copper sulfate pentahydrate, disodium ethylenediaminetetraacetate and sodium tartrate is 1:1:2; and the material-liquid ratio of copper sulfate pentahydrate-disodium ethylenediaminetetraacetate-sodium tartrate and deionized water is 1:

3.

7. The copper-based thermal conductive material according to claim 5, characterized in that: In step S22, the amount of modified graphene or silicon carbide added is 40-50% of the mass of the dissolving solution; the amount of formaldehyde solution used is 8 ml / L.

8. The copper-based thermal conductive material according to claim 1, characterized in that: The particle size of the copper powder is 4-5 μm; the particle size of the coated modified graphene is 1-2 μm; and the particle size of the coated silicon carbide is 2-3 μm.

9. The method for preparing the copper-based thermal conductive material according to any one of claims 1 to 8, characterized in that: Specifically, the coated modified graphene, coated silicon carbide and copper powder are stirred and mixed to prepare a copper-based thermal conductive material.